Improvement of training students’ information profile in the field of databases - Bazikova, K.M.; Kazimova, D.A.; Kitibayeva, A.K.; Mikhaylova, N.B. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with improvement of training students’ information profile in the field of databases. The basic aspects of the use of information technology in the formation of professional competencies of a modern specialist are defined. It has been described the substantial components of the discipline of choice "Programming MS SQL". The focus of the study of this course is given to the development and use of the database.
Мəлімет қорлар аймағында ақпараттық бағыты бойынша студенттердің дайындығын жетілдіру
Совершенствование подготовки студентов информационного профиля в области баз данных
Keywords: training; students; information specialty; database; information technology; professional competences; contemporary specialist; optional discipline; sphere of the development; the language of SQL